Penilaian Kinerja Pegawai Lingkungan Perguruan Tinggi dengan Metode Topsis - Setyadi, Ary; Adi, Kusworo; Sugiharto, Aris (Universitas Diponegoro, 2012)
Employee performance measurement is very important for evaluation and future planning. Most of the government and private agencies are still using Daftar Penilaian Pelaksanaan Pekerjaan (DP3) to assess the performance their employees. DP3 goal is to obtain an objective consideration to employee development and career system based on job performance, formally it used to be a principal consideration material of periodic salary increases and promotions. In this research made ​​a Decision Support System (DSS) for employee performance appraisal DP3 at the college by using TOPSIS method. In this DSS ​​of which there are eight criteria in the DP3, everything is broken down into several sub criteria to get more objective assessment. Initial input of the TOPSIS method is obtained through a calculation using the AHP to find the eigen value of each criterion and the intensity. System created to describe the process of AHP and TOPSIS at each step in a matrix that can be studied and evaluated the truth of each step in the method used. In testing, this system is quite effective in the calculation that uses looping and selection. Keywords: TOPSIS, employee performance evaluation, DP3